Dual opposing quadrature-PT symmetry - Wencong Wang; Jacob Kokinda; Jiazhen Li; Qing Gu; Dongmei Liu; Jianming Wen (iScience)
Summary: Our recent research on type-I quadrature parity-time (PT) symmetry, utilizing an open twin-beam system, not only enables observing genuine quantum photonic PT symmetry amid phase-sensitive amplification (PSA) and loss in the presence of Langevin noise but also reveals an additional classical-to-quantum (C2Q) transition in noise fluctuations. In contrast to the previous setup, our exploration of an alternative system assuming no loss involves a type-II PSA-only scheme. This scheme facilitates dual opposing quadrature-PT symmetry, offering a comprehensive and complementary comprehension of C2Q transitions and PT-enhanced quantum sensing with optimal performance in the symmetry unbroken region. Furthermore, our investigation into the quantum correlation with the Einstein-Podolsky-Rosen criteria uncovers previously unexplored connections between PT symmetry and nonclassicality, as well as quantum entanglement within the continuous-variable framework.